Recovering Hydrogen Sulfide from Sulfurous Waters with PEM Fuel Cells. (January 2016) - Iordache, S.M.; Ciocanea, A.; Balan, A.; Stamatin, I.; Budea, S.; Ceaus, C.; Trefilov, A.M.I.; Voinea, S.
Abstract: Hydrogen sulfide is an environmental pollutant and abundant in various sulfurous waters such as Black Sea. Hydrogen sulfide is in the same time a potential energetic materials as source for hydrogen production. In this respect, designing an appropriate fuel cell with proton exchange membranes (PEMFC) for hydrogen sulfide recovering from sulfurous water is challenge. This study reports a PEMFC with Pt/Pt-Ru catalysts and membrane with perflurosulfonic ionomer. PEMFC was run at different concentrations of hydrogen sulfide in water (50-150 mg/L). Even though power densities are in the range microwatts the experimental set-up shows a promising perspective for sulfurous water treatment. A short overview on the actual state of the art in hydrogen sulfide recovering and potential applications of the fuel cells is presented in introduction.